Eco-Critical Discourse Analysis of Regional Slogans in Central Java Province - Puspita Sari, Kharisma; Kadarismanto, Kadarismanto (Universitas Negeri Semarang, 2025)
Slogan is short word or phrase that is easy to remember. The current researcher spotted 32 slogans from the regencies in Central Java Province. These slogans has been displayed by using descriptive analysis. The writer employed chosen sampling in exploring the regional slogans as the main data. Obediently, the researcher concluded that the findings of this research was mostly regional places in Central Java Province injected the term of ecofriendly spirit in their slogans. The findings researcher found that 23 regencies intelligibly announced eco-friendly concepts in their slogans and jargon while nine regencies did not comprehensibly state their eco-friendly projects. Furthermore, the researcher detected four common hopes and missions in which their eco-friendly programs as like Bersih/Unspotted, Sehat/Vigorous, Rapi/Immaculate, Indah/Aesthetic, and Nyaman/Comfy. Besides, there would be three specific eco-friendly terms in detectable slogans such as Asri/Far from Air Pollution, Hijau/Green, and Lestari/Everlasting. Last, the researcher hoped that every regency in Indonesia injected eco-friendly principles in their mottos and urban planning to realize ecology persistence in Bumi Pertiwi, Indonesian Country.